The Problem of Emotional Impact on Populist Discourse - حليم نورالدين; بومزبر الطاهر (Milev Journal of Research and Studies, 2023)
The follower of the evolution of the expression of emotions over time note clearly that emotion has become strongly assumed by political actors, that is why research paper seeks to trace its impact on the populist discourse by distinguishing between its traditional concept in the fields of psychology and sociology, and the new concept that it acquired in the field of discourse analysis on the one hand, and an attempt to monitor some strategies of emotional influence (patos) through which it is possible to judge the popularity of the discourse on the other hand.